PENGGUNAAN MEDIA PREZI DESKTOP FOREVER UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA TRI BHAKTI PEKANBARU - Rizka Putri Perjuwanda Putri Perjuwanda; R Usman Rery Rery; Betty Holiwarni Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase student achievement on the subject Koloid in class XI SMA Tri Bhakti Pekanbaru. This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMA Tri Bhakti Pekanbaru. The samples of this research were the students of class XI 2 as the experimental class and students of class XI 1 as the control class. Experimental class is a class that is applied the use of media Prezi while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,42 > 1,67, means that the use of Prezi Desktop Forever can improve student achievement on the subject of koloid class XI SMA Tri Bhakti Pekanbaru, increase learning of 8%. Keywords : Learning Achievement, Prezi Desktop Forever, and Koloid